Analisa DFA Terhadap Rancangan Body Mesin Pencacah Plastik - Galih Afrizal; Subkhan Subkhan; Yang Fitri Arriyani (Jurnal Inovasi Teknologi Terapan, 2026)
Efficient product design not only focuses on functionality and structural strength but also emphasizes the ease of the assembly process. This study aims to analyze the application of the Design for Assembly (DFA) method in the body design process of a product to achieve a more efficient and easily assembled structure. The DFA method is used to evaluate the number of components, assembly sequence, assembly time, and the level of difficulty in installing each component. The analysis compares several body design alternatives based on criteria such as manufacturability, ease of maintenance, and assembly efficiency. The results show that the application of DFA principles can reduce unnecessary components, minimize assembly time, and improve structural efficiency by more than 20%. Therefore, implementing the Design for Assembly concept at the design stage can produce a simpler, more economical, and easily assembled product body without compromising its strength or functionality.